Effects of Wire EDM on the Microstructure of P/M Titanium Samples - Joško Viskić; Zdravko Schauperl; Amir Ćatić; Martin Balog; Peter Krizik; Biserka Gržeta; Jasminka Popović; Slađana MILARDOVIĆ ORTOLAN; Ketij Mehulić (University of Zagreb. School of Dental Medicine, 2014)
Purpose: Commercially pure titanium (CP Ti) has been recognized in dentistry for its biocompatibility, good mechanical properties and corrosion resistance. Conventional manufacturing processes can affect surface quality and result in poor bonding of dental ceramics to CP Ti. This is why powder metallurgy (P/M) and wire electro-discharge machining (WEDM) are being introduced in the manufacturing process. The aim of this study was to evaluate the effect of WEDM on the surface composition and microstructure of P/M CP Ti samples produced for bond strength testing according to ISO 9693. Materials and methods: Eight samples of P/M CP Ti, dimensions according to ISO 9693, were made using WEDM and divided in two groups (untreated and grinded). Microanalyses of chemical composition and microstructure of both groups were made using SEM, EDS and XDR. Results: SEM and EDS analysis of untreated samples showed a thin layer on surfaces with fractures in it. Grinded samples showed homogenous structure with no layer and no fractures. XDR analysis showed high level of oxides on the surface of untreated samples, while after grinding only pure α-phase was found. Conclusion: WEDM is a suitable method of sample production for ISO 9693 if accompanied by grinding with silicon carbide papers P320-P4000.